The Effects of Self-development, Self-therapy, and Self-presentation Motivations on Quality of Life, Visitor Loyalty, and Omnivorous Cultural Engagement through Visitor Satisfaction in Art Museums: Examining the Moderation Effect of Age and Attitude toward SNS Posting - Yi, Minyeong; La, Suna (Asia Marketing Journal (Online), 2023)
This study investigates the fulfillment of self-motivation including self-development, self-therapy, and self-presentation on the outcomes such as subjective quality of life, omnivorous cultural engagement, and visitor loyalty via visitor satisfaction in art museums. The analyses on 285 valid survey responses demonstrated that fulfillment of self-development and self-therapy needs have significant positive influence on visitor satisfaction. The effect of fulfilling self-presentation need on visitor satisfaction was found to be moderated by attitude toward SNS posting, while the age factor, based on generations, did not show a significant moderation effect. It was also found that visitor satisfaction positively influences visitor loyalty, including intentions of revisit and recommendation. Increased satisfaction also enhances subjective QOL and omnivorous cultural engagement among art museum visitors, implying promising collaboration among cultural arts institutions. The findings have both theoretical and practical implications for enhancing visitor experiences and promoting diverse cultural engagement. Limitations and future research directions are also discussed.